Harnessing outdoor learning in primary science education: impact on developing technological innovations for waste management and sustainability awareness - Wardani, Duhita Savira; Widodo, Ari; Syaodih, Ernawulan; Muslim (Frontiers in Sustainability, 2026)
Sustainability education in primary schools is often dominated by classroom-based and theoretical instruction, which limits students’ sustainability awareness and their ability to develop practical technological solutions to real-world environmental problems, particularly in waste management. This study explores the impact of outdoor learning programs in fostering sustainability awareness and encouraging technological innovations in waste management among elementary school students. Conducted at a “Self-managed Waste Village,” the research integrates experiential learning with problem-based activities, focusing on students’ direct engagement with authentic environmental challenges. Using a quantitative research design, data were collected from 299 students through sustainability awareness questionnaires and rubrics for evaluating technological products. Structural Equation Modeling (SEM) was employed to examine direct and mediating relationships among outdoor learning, sustainability awareness, and technological innovation. The results indicate that outdoor learning is positively associated with students’ sustainability awareness and shows a significant relationship with their technological innovation outcomes. Sustainability awareness is also significantly related to students’ ability to design innovative waste management solutions, with outdoor learning acting as a mediating factor in this relationship. These findings highlight the potential role of outdoor learning as a pedagogical approach associated with the development of sustainability awareness and technological creativity in primary science education.